Pesantren in Indonesia and Sustainable Development Issues - Syahdatul Maulida; Mohammad Mahbubi Ali (SMART Insight, 2023)
This paper aims to observe the evolution of research focusing on Pesantren and sustainable development issues published in various journals around the world. The method used is a qualitative approach with bibliometric analysis using R software. The data used are secondary data related to the theme